Предмет: Алгебра,
автор: likemycat
Решите уравнение: x(x-3)+x(2x-1)=3x(x-2)-3
Ответы
Автор ответа:
0
Решение на фотографии.
Приложения:
Автор ответа:
0
Спасибо ты очень помог!
Автор ответа:
0
x(x-3)+x(2x-1)=3x(x-2)-3 ,⇒ x²-3x+2x²-x=3x²-6x-3,⇒ 3x²-4x=3x²-6x-3,⇒3x²-4x-3x²+6x+3=0⇒
⇒2x+3=0⇒2x=-3⇒x=-1,5 ответ:-1,5
⇒2x+3=0⇒2x=-3⇒x=-1,5 ответ:-1,5
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: Kotobormotik
Предмет: Русский язык,
автор: ddddggggs
Предмет: История,
автор: KlubNi4kO